2018
DOI: 10.14238/pi57.5.2017.223-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nigella sativa oil on Th1/Th2, cytokine balance, and improvement of asthma control in children

Abstract: Background Asthma is a chronic inflammatory disease of the airways characterized by involvement of a variety of inflammatory cells. Asthma is associated with imbalances between Th1/Th2 cells and their characteristic cytokine profiles. Nigella sativa is a plant that possesses immunomodulatory and anti-inflammatory properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Several mechanisms of action have been suggested for N. sativa extracts. In the present study, the inhibition of the production of GC-insensitive chemokines (CCL5, CXCL-8, and CXCL-10) induced by TNF-α and IFN-γ may involve the mechanism of Th1/Th2 cytokine modulation, which is attributed to the inhibition of the signal transducer and activator of transcription-6 (STAT6) signaling pathway [49,50].…”
Section: Discussionmentioning
confidence: 67%
“…Several mechanisms of action have been suggested for N. sativa extracts. In the present study, the inhibition of the production of GC-insensitive chemokines (CCL5, CXCL-8, and CXCL-10) induced by TNF-α and IFN-γ may involve the mechanism of Th1/Th2 cytokine modulation, which is attributed to the inhibition of the signal transducer and activator of transcription-6 (STAT6) signaling pathway [49,50].…”
Section: Discussionmentioning
confidence: 67%
“…NS oil administration reduced the percentage of CD8+ T cells and increased CD4+CD25+ T cells and the CD4+/CD8+ ratio compared to RA patients treated with placebo and baseline results. Another study showed that NS oil affects Th1/Th2 cytokine balance and improves asthma control in children [76]. Children in this study were given 15-30 mg/kg/day of NS oil for eight weeks.…”
Section: Studies In Vivomentioning
confidence: 88%
“…These results could suggest that NSEO shifts the T cell response toward Th2, as evidenced by the increased IL-4 levels. Barlianto et al [ 55 ] obtained the opposite effect while examining the effect of NS oil supplementation in children with asthma. The authors demonstrated that 8 weeks of NS oil supplementation increases serum IFN-γ levels and reduces IL-4 levels, thus redirecting the T cell response toward Th1.…”
Section: Discussionmentioning
confidence: 99%